High-yield on-demand production of tobacco mosaic virus-like particles using a plant-derived cell-free expression system - Große, David H. B.; Buhl, Eva M.; Croon, Alexander; Schillberg, Stefan; Schuphan, Juliane (Frontiers in Nanotechnology, 2025)
Plant virus nanoparticles (VNPs) can be used to generate versatile, functionalized nanomaterials, but they contain replicative genomic DNA whose impact on the environment must be assessed carefully. In contrast, plant virus-like particles (VLPs) lack replicative genomic information and are therefore non-infectious. However, the production of VLPs in plants is associated with challenges such as low yields and a purification process that is difficult to scale up. To address these issues, we used cell-free lysates derived from Nicotiana tabacum BY-2 cells to produce tobacco mosaic virus (TMV)-like particles. The objective of this approach was to generate VLPs with and without encapsulated RNA. SDS-PAGE and Western blotting indicated the accumulation of abundant quantities of the viral coat protein, with yields of up to 3.56 ± 0.62 mg per ml of cell-free lysate confirmed by enzyme-linked immunosorbent assay before purification. The yield of purified TMV VLP is comparable to that obtained from plants due to the low assembly efficiency, with assembled VLPs yielding up to 0.70 ± 0.16 mg per ml of lysate. Notably, this yield is approximately 23 times higher than that obtained through microbial expression systems, obviating the need for the labor-intensive processes typically associated with plant-based methods. Transmission electron microscopy revealed that VLPs assembled in the lysate at pH 7, and remained stable at up to pH 8.5. Cell-free expression therefore offers a rapid, straightforward and cost-effective method for the production of plant VLPs at high yields, and establishes a foundation for the on-demand production of functionalized VLPs under controlled and reproducible conditions.